2019
DOI: 10.1093/toxsci/kfz182
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Induced Dysregulation of Neuroendocrine Axes Requires Adrenal-Derived Stress Hormones

Abstract: Acute ozone inhalation increases circulating stress hormones through activation of the sympathetic-adrenal-medullary and hypothalamic-pituitary-adrenal axes. Rats with adrenalectomy (AD) have attenuated ozone-induced lung responses. We hypothesized that ozone exposure will induce changes in circulating pituitary-derived hormones and global gene expression in the brainstem and hypothalamus, and that AD will ameliorate these effects. Male Wistar-Kyoto rats (13 weeks) that underwent sham surgery (SHAM) or AD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…The increases in 7-HOCA after ozone exposure might also be linked to gut microbiome changes since gut microbes are involved in production of secondary bile acids and 7-HOCA is an intermediate in this process 56 . Gut microbiome changes due to maternal diet and acute ozone exposure may underlie the marked changes in brain and neuroendocrine pathways after ozone exposure 10,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The increases in 7-HOCA after ozone exposure might also be linked to gut microbiome changes since gut microbes are involved in production of secondary bile acids and 7-HOCA is an intermediate in this process 56 . Gut microbiome changes due to maternal diet and acute ozone exposure may underlie the marked changes in brain and neuroendocrine pathways after ozone exposure 10,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of epinephrine are also increased following O 3 (19, 21, 31) and remain elevated even 18 h after cessation of exposure (21). These changes in stress hormones are thought to arise from O 3 -induced stimulation of sensory afferents within the lungs and nose (32). These afferents have been shown to terminate in stress responsive regions of the brain (33).…”
Section: Mechanistic Basis For the Metabolic Effects Of O3mentioning
confidence: 99%
“…Our recent study has shown that acute ozone exposure induces a wide array of gene expression changes in the brain stem and hypothalamus that are similar to those induced during hypoxia (ie, interferon signaling and the activation of stress pathways). 128 These ozone-induced gene expression changes in rats are associated with increases in adrenaline and corticosterone while depleting prolactin, luteinizing hormone, and also thyroid-stimulating hormone, suggesting the concomitant inhibition of hypothalamus–pituitary–gonadal (HPG) and hypothalamus–pituitary–thyroid (HPT) axes. The activation of SAM and HPA and associated inhibition of HPG and HPT axes have been reported after application of other stressors.…”
Section: Linking Peripheral Metabolic and Immune Effects Of Irritant mentioning
confidence: 99%
“…Circulating stress hormones are needed to produce lung effects of ozone, and if no lung effects occur due to lack of stress hormones, no changes in brain regions are noted. 128 Glucocorticoids in conjunction with mineralocorticoids and catecholamines have been shown to interactively regulate the process of adaptation and habituation centrally. 99 The regulatory roles of adrenergic and glucocorticoid receptors systems and feedback inhibition need to be further examined in relation to health effects of acute and chronic air pollution exposures and more importantly how neuroendocrine response variations may lead to variations in human susceptibility to air pollution health effects.…”
Section: Linking Peripheral Metabolic and Immune Effects Of Irritant mentioning
confidence: 99%
See 1 more Smart Citation